HUBUNGAN PARITAS DAN JARAK KEHAMILAN DENGAN BERAT BADAN LAHIR BAYI DI PUSKESMAS MAMBORO - Eunike Syerin Glori Baan (Jurnal Medika Hutama, 2026)
Infant mortality rate (IMR) is a parameter used for measuring a country’s health status, with the majority of deaths occurring during the neonatal period. Low birth weight, which refers to infants weighing under 2500 grams at birth, accounts for approximately 34.5% of a factor contributing to neonatal mortality. Infant birth weight is influenced by maternal factors, including parity and birth spacing. Low birth weight cases at Mamboro Health Center remain a concern, with more than 20 cases in 2024, particularly because the area still includes a rural community. This research aims to analyze the relationship between parity and birth spacing with birth weight at Puskesmas Mamboro in 2024. This study used a quantitative analytical observational design, with 69 samples. The data were then analyzed using the Chi-square test. The result showed a relationship between parity and birth weight (p=0,003), with multiparous mothers having a lower risk of delivering low birth weight. Meanwhile, there was no significant relationship between pregnancy spacing and birth weight (p= 0,226). Although not statistically significant, the proportion of low birth weight cases was more common at too short and too long intervals compared with ideal intervals.